2017
DOI: 10.1177/0959683617721331
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation dynamics and fire history at the southern boundary of the forest vegetation zone in European Russia during the middle and late Holocene

Abstract: Climate and human activity affected significantly the Eurasian on the forest vegetation zone through the Holocene. This paper presents new multi-proxy records of environmental changes at the southern boundary of the mixed coniferous-broadleaf forest zone in the eastcentral part of the East European Plain during the middle and late Holocene. Palaeoecological analyses of a peat core for pollen, charcoal, peat humification, plant macrofossils and testate amoebae with dating using radiocarbon have shown that clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…According to historical documents and observations of the Mordovia State Nature Reserve staff, significant wildfire evidences in the Protected Area have been recorded in 1842, 1899, 1932, 1972 and 2010 (Kuznetsov, 1960;Grishutkin, 2012). The frequency and intensity of fires has increased precisely in the last two centuries in accordance with paleoecological data (Sieber et al, 2013;Novenko et al, 2018;Šamonil et al, 2018;Stambaugh et al, 2018). The 2010 fires were especially significant, as their area was 38% of the total area of the Mordovia Reserve.…”
Section: Introductionsupporting
confidence: 70%
“…According to historical documents and observations of the Mordovia State Nature Reserve staff, significant wildfire evidences in the Protected Area have been recorded in 1842, 1899, 1932, 1972 and 2010 (Kuznetsov, 1960;Grishutkin, 2012). The frequency and intensity of fires has increased precisely in the last two centuries in accordance with paleoecological data (Sieber et al, 2013;Novenko et al, 2018;Šamonil et al, 2018;Stambaugh et al, 2018). The 2010 fires were especially significant, as their area was 38% of the total area of the Mordovia Reserve.…”
Section: Introductionsupporting
confidence: 70%
“…In addition, the lack of water bodies negatively influences Odonata, Lepidoptera, and Mollusca. Second, the central and eastern parts of the Mordovia State Nature Reserve have been damaged by humans, as also indicated by palaeobotanical data (see Novenko et al 2017). In these parts of the Protected Areas, broad-leaved forests have been changed into pine forests, wildfires became more frequent and Picea abies started penetrating into the forest communities.…”
Section: Resultsmentioning
confidence: 91%
“…The composition and structure of mid to late Holocene vegetation of the eastern Lower Danube Plain resembled, to a large degree, that of other European forest steppe areas, although particularities also exist. Whilst in central eastern European forest steppe, Quercus and Carpinus betulus were the dominant tree species with a lower occurrence of Tilia, Ulmus, Corylus and Pinus (Magyari et al, 2010;Feurdean et al, 2015;Kuneš et al, 2015), on the Eastern European Plain, Tilia and Quercus, and in some places Pinus, were the dominant tree taxa (Kremenetski et al, 1995;Novenko et al, 2016Novenko et al, , 2018Shumilovskikh et al, 2018Shumilovskikh et al, , 2019. Forests in the Black Sea region also included thermophilus taxa i.e., Quercus cerris, C. orientialis (this study, Marinova et al, 2006;Tonkov et al, 2014) Remarkably, Carpinus orientalis was found to be significantly more abundant around the Black Sea coast i.e., Romania (20%), Bulgaria (>5%), or with only scattered occurrences in Ukraine, whilst it was absent from Central European forest steppe.…”
Section: Comparison With Other European Forest Steppe Regionsmentioning
confidence: 99%